Determination of Tax Officer's Motivation and Competence on Taxpayer Compliance and Revenue Performance - Mochamad Saprudin; Hapzi Ali (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This article reviews the effect of employee motivation and competence on taxpayer compliance and revenue performance. This study aims to build a hypothesis of the influence of variables used during the study. The research was conducted through the distribution of questionnaires/surveys and library research with the following results: 1) Motivation affects taxpayer compliance, 2) Motivation has an effect on Revenue Performance, 3) Competence has an effect on Taxpayer Compliance 4) Competence has an effect on Revenue Performance 5) Taxpayer Compliance affects Revenue Performance.